Chemical and photochemical behavior of ruthenium nitrosyl complexes with terpyridine ligands in aqueous media. Issue 10 (20th February 2020) - Labra-Vázquez, Pablo; Bocé, Mathilde; Tassé, Marine; Mallet-Ladeira, Sonia; Lacroix, Pascal G.; Farfán, Norberto; Malfant, Isabelle
Abstract : The synthesis and behavior in water of a set of various cis (Cl, Cl)-[R-tpyRuCl2 (NO)](PF6 ) and trans (Cl, Cl)-[R-tpyRuCl2 (NO)](PF6 ) (R = fluorenyl, phenyl, thiophenyl; tpy = 2, 2′:6′, 2′′-terpyridine) complexes are presented. Abstract : The synthesis and behavior in water of a set of various cis (Cl, Cl)-[R-tpyRuCl2 (NO)](PF6 ) and trans (Cl, Cl)-[R-tpyRuCl2 (NO)](PF6 ) (R = fluorenyl, phenyl, thiophenyl; tpy = 2, 2′:6′, 2′′-terpyridine) complexes are presented. In any case, one chlorido ligand is substituted by a hydroxo ligand and the final species arises as a single trans (NO, OH) isomer, whatever the nature of the starting cis / trans (Cl, Cl) complexes. Six X-ray crystal structures are presented for cis (Cl, Cl)-[thiophenyl-tpyRuCl2 (NO)](PF6 ) ( cis -3a ), trans (Cl, Cl)-[thiophenyl-tpyRuCl2 (NO)](PF6 ) ( trans -3a ), trans (NO, OH)-[phenyl-tpyRu(Cl)(OH)(NO)](PF6 ) (4a ), trans (NO, OH)-[thiophenyl-tpyRu(Cl)(OH)(NO)](PF6 ) (4b ), trans (NO, OEt)-[phenyl-tpyRu(Cl)(OEt)(NO)](PF6 ) (5a ), and trans (NO, OH)-[phenyl-tpyRu(Cl)(OEt)(NO)](PF6 ) (5b ) compounds. The different cis / trans (Cl, Cl) complexes exhibit an intense low-lying transition in the λ = 330–390 nm range, which appears to be slightly blue-shifted after Cl → OH substitution. In water, both cis / trans (Cl, Cl) isomers are converted to a single trans (NO, OH) isomer in which one chlorido- is replaced by one hydroxo-ligand, which avoids tedious separation workout. The water stable trans (NO, OH)-species all release NO with quantum yields of 0.010 to 0.075 under irradiation at 365 nm. The properties are discussed with computational analysis performed within the framework of Density Functional Theory.